2012
DOI: 10.1039/c2ce06404a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of magnetic field on dealloying of Al-25Ag alloy and formation of nanoporous Ag

Abstract: The dealloying behavior of bi-phase Al-Ag alloys in 5 wt.% HCl in non-treated and magnetic treated conditions was comparatively investigated. The as-dealloyed samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) analysis coupled with SEM. The results reveal that an external magnetic field would accelerate the dealloying process and the as-dealloyed samples from magnetic treatment are characterized by a finer and more homogeneous three dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…The ultrasonic agitation reduced the time by a factor of 5 without disturbing the desired structure. There has been a similar effect of the magnetic field highlighted on the nanopores of Ag [24].…”
Section: Fabrication Methodsmentioning
confidence: 71%
“…The ultrasonic agitation reduced the time by a factor of 5 without disturbing the desired structure. There has been a similar effect of the magnetic field highlighted on the nanopores of Ag [24].…”
Section: Fabrication Methodsmentioning
confidence: 71%
“…The ligaments of acid-treated samples have a diameter of about 115–130 nm, but only about 65–80 nm for NaOH-treated samples. In ref ( 30 ), the authors used a Ag 25 Al 75 alloy and obtained ligaments of different sizes by treating it with 5 wt % HCl at different temperatures and times. They concluded that the surface diffusion of Ag is an activated process according to the Arrhenius law with an activation energy of 75.66 kJ mol –1 and a pre-exponential factor D o = 4.432 × 10 –4 m 2 s –1 .…”
Section: Resultsmentioning
confidence: 99%
“…The surface diffusion coe cient, Ds, is related to the ligament size, d, according to the following equation [52][53][54]:…”
Section: Bonding Mechanisms Of Npc/cu Joints Under Different Atmospheresmentioning
confidence: 99%